2015
DOI: 10.4049/jimmunol.1402508
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Systemic Spread Determines CD8+ T Cell Immunodominance for Laboratory Strains, Smallpox Vaccines, and Zoonotic Isolates of Vaccinia Virus

Abstract: CD8+ T cells that recognize virus-derived peptides presented on MHC class I (pMHC) are vital anti-viral effectors. The pMHC presented by any given virus vary greatly in immunogenicity allowing them to be ranked in an immunodominance hierarchy. However, the full range of parameters that determine immunodominance and the underlying mechanisms remain unknown. Here we show across a range of vaccinia virus (VACV) strains, including the current clonal smallpox vaccine, that the ability of a strain to spread systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Viral load and antigen abundance have been shown by others to influence the magnitude of CD8 + T cell responses suggesting a role in determining immunodominance hierarchy (16, 37). However, we have previously demonstrated that intranasal infection of neonates and adults with a replication-defective adenovirus vector expressing the K d M2 82–90 and D b M 187–195 epitopes does not alter either immunodominance hierarchy (22).…”
Section: Resultsmentioning
confidence: 99%
“…Viral load and antigen abundance have been shown by others to influence the magnitude of CD8 + T cell responses suggesting a role in determining immunodominance hierarchy (16, 37). However, we have previously demonstrated that intranasal infection of neonates and adults with a replication-defective adenovirus vector expressing the K d M2 82–90 and D b M 187–195 epitopes does not alter either immunodominance hierarchy (22).…”
Section: Resultsmentioning
confidence: 99%
“…Systemic (i.p., or i.v.) or respiratory inoculation of immunocompetent mice with the mouse adapted Western Reserve strain (VacV-WR) results in an acute infection during which the virus replicates very rapidly to high titers, causes strong and sustained inflammation, and disseminates to multiple lymphoid and non-lymphoid tissues within the host ( 1 4 ). Activated macrophages ( 5 ), natural killer (NK) cells ( 6 , 7 ), and γδ T cells ( 8 ) play an important role in the initial control of VacV ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…This published treatment eliminates infectivity and de novo viral gene expression and presentation in vivo , as shown by the complete loss of responses to VACV-encoded minimal epitope constructs that require direct presentation to prime CD8 + T cells ( 22 , 24 ). The CD8 + T cell response to a well-characterized panel of major VACV epitopes was then measured at the peak of the acute response by ex vivo stimulation of splenocytes with synthetic peptides and intracellular staining for gamma interferon (IFN-γ) ( 19 , 26 28 ). A subset of the epitopes that were published as being immunogenic after immunization of HI virus-infected cells were also found to elicit responses here, the difference mostly likely reflecting different routes of immunization ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This can be especially important in prime-boost strategies where initial immunization with HI rVACV can generate large pools of CD8 + T cells toward the vaccine epitopes that then have an advantage in a subsequent live VACV boost. We note that, for HI VACV, we eliminate presentation of the immunodominant B8 20 epitope and other strategies that reduce responses to this peptide tend to allow greater expansion of CD8 + T cells primed by less dominant specificities ( 27 , 28 ). In our prime-boost experiment ( Fig.…”
Section: Discussionmentioning
confidence: 99%